2018
DOI: 10.1089/jwh.2016.6276
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Violence as a Key Contributor to Poor Mental Health Among Japanese Women Subjected to Intimate Partner Violence

Abstract: The present research showed that significant adverse effects on mental health were observed among women who experienced IPV with sexual violence compared with the ones without. These findings provide important implications for considering the specific approaches to meet the needs of those women experiencing sexual IPV and the need for timely and effective interventions, including healthcare, social services, and primary prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…In line with previous research findings (Issahaku, 2015;Hahm et al, 2017;Honda et al, 2018;Pengpid et al, 2018), these women who had experienced abusive relationships reported physical pain, a low level of self-esteem and self-worth, depression and trauma-related symptoms. A sense of disempowerment occurred in particular when they felt that there was nobody to help them and they had nowhere to go.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with previous research findings (Issahaku, 2015;Hahm et al, 2017;Honda et al, 2018;Pengpid et al, 2018), these women who had experienced abusive relationships reported physical pain, a low level of self-esteem and self-worth, depression and trauma-related symptoms. A sense of disempowerment occurred in particular when they felt that there was nobody to help them and they had nowhere to go.…”
Section: Discussionsupporting
confidence: 90%
“…Intimate partner sexual violence (IPSV) is grave in nature, and it can cause several mental and/or physical health problems or disabilities. Researchers have found that women who have experienced sexual violence by a partner might suffer from PTSD (Bennice et al, 2003;Kessler et al, 2017;Zakrison et al, 2017;Honda et al, 2018), depression (Davhana-Maselesele et al, 2014;Honda et al, 2018), anxiety (Jaquier et al, 2015;Honda et al, 2018), substance and alcohol abuse (Decker et al, 2014;Jaquier et al, 2015;Hahm et al, 2017;Pengpid et al, 2018), somatic symptoms (Honda et al, 2018), sleep problems (Issahaku, 2015), and suicidal ideation and/or attempt (Sedziafa et al, 2016;Honda et al, 2018;Pengpid et al, 2018). They might also experience an unwanted pregnancy, abortion, being infected with HIV, and experience other forms of physical issues such as facial injuries, physical weakness, hypertension, and genital problems (Sedziafa et al, 2016).…”
Section: " I Had To Do That [What They Saw On Porn Clip] … I Didn't Hmentioning
confidence: 99%
“…Most of the literature on exposure to violence is either in the community, clinical, or correctional settings [ 5 , 38 , 39 , 40 , 41 , 42 ], with very few studies available on mental health correlates of history of exposure to violence on college campuses. Individuals experience various forms of violence, which include physical, psychological, and sexual abuse [ 43 , 44 ]. Regardless of type of violence [ 44 ], victims of violence are at a higher risk of poor psychological outcomes [ 7 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, most of the research on IPV has focused on psychological (IPV in the forms of stalking, psychological aggression, and verbal abuse that are not physical or sexual) and physical forms of violence [ 2 , 3 , 4 , 5 , 6 ]. As a result, our knowledge of psychological and behavioral risk factors of sexual IPV among ethnic minority women is very limited [ 7 ]. Second, the majority of the existing literature on psychosocial risk factors of IPV among minorities has used a cross-sectional design.…”
Section: Introductionmentioning
confidence: 99%